2015
DOI: 10.1016/j.egypro.2015.03.135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heliostat Field Layout Design Methodologies and Impact on Power Plant Efficiency

Abstract: The aim of this paper is the presentation of a study of heliostat field layout performances for a CSP plant, based on the central receiver technology, using different algorithms for layout generation. The purpose is to perform a detailed comparison of the layout performances in terms of efficiency and energy yield to determine the algorithms benefits and drawbacks at various scenarios as first step on the optimization of the heliostat layouts designs. The layouts compared are generated using a genetic optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This distribution pattern is also characterized by achieving a good trade-off between land use and field efficiency. For instance, in Mutuberria et al (2015), its good properties are also observed. The method is inspired by the spiral patterns of the phyllotaxis disc, like florets on the head of sunflowers.…”
Section: Biomimetic Distribution Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…This distribution pattern is also characterized by achieving a good trade-off between land use and field efficiency. For instance, in Mutuberria et al (2015), its good properties are also observed. The method is inspired by the spiral patterns of the phyllotaxis disc, like florets on the head of sunflowers.…”
Section: Biomimetic Distribution Modelmentioning
confidence: 92%
“…10), and the biomimetic spiral, recently proposed by Noone et al (2012), are two examples of patterns. In Mutuberria et al (2015), where several patterns are compared, more examples and references can be found. The second strategy is to select final heliostat positions from a defined set (as iteratively done in Sánchez and Romero, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In [18], it is proposed an innovative bio-inspired pattern based on a Fermat spiral. That layout has become really popular: it has been used, for instance, in [3], and successfully compared to other patterns [17,32]. To attenuate their rigidity, patterns are often applied to generate oversize fields before finally selecting the minimum required heliostats [3,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, its simple and parallel structure aims to be a valuable component of a complete field design methodology. Although genetic algorithms have already been used for heliostat field optimization, the focus is usually on reduced sets of parameters as in [3,17,19,20]. Similarly, the use of high-performance computing is not a new proposal of this work.…”
Section: Introductionmentioning
confidence: 99%
“…A classic and popular one is radial staggering [17], which inspires some recent proposals [13,9,18]. An example of modern pattern is the spiral proposed in [7], which has attracted the interest of several researchers [19,20,21]. Regarding the iterative deployment of heliostats, the work in [10] is one of the most popular ones.…”
Section: Introductionmentioning
confidence: 99%